2002
DOI: 10.1523/jneurosci.22-03-00666.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specificity of Gαqand Gα11in the Cholinergic and Glutamatergic Modulation of Potassium Currents and Excitability in Hippocampal Neurons

Abstract: In hippocampal and other cortical neurons, action potentials are followed by a slow afterhyperpolarization (sAHP) generated by the activation of small-conductance Ca 2ϩ -activated K ϩ channels and controlling spike frequency adaptation. The corresponding current, the apamin-insensitive sI AHP , is a well known target of modulation by different neurotransmitters, including acetylcholine (via M 3 receptors) and glutamate (via metabotropic glutamate receptor 5, mGluR 5 ), in CA1 pyramidal neurons. The actions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 61 publications
5
43
0
Order By: Relevance
“…In CA1 pyramidal cells, the G-protein G␣ q is responsible for the modulation of I sAHP by muscarinic and glutamatergic agonists (Krause et al, 2002). We performed coimmunoprecipitation experiments to determine whether native KARs are associated with G␣ q , using an antibody that recognizes both G␣ q and G␣ 11.…”
Section: Resultsmentioning
confidence: 99%
“…In CA1 pyramidal cells, the G-protein G␣ q is responsible for the modulation of I sAHP by muscarinic and glutamatergic agonists (Krause et al, 2002). We performed coimmunoprecipitation experiments to determine whether native KARs are associated with G␣ q , using an antibody that recognizes both G␣ q and G␣ 11.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, basal hippocampal ACh levels in situ are not only reduced in aged F344 rats, but both BIBN-99 and the structurally related M 2 blocker AF DX384 (Ϯ)-5,11 [2,3-b](1,4)-benzodiazepine-6-one) have been shown to elevate hippocampal ACh levels more robustly in aged than young subjects (Quirion et al, 1995;Vannucchi et al, 1997). Blockade of M 2 receptors on ACh terminals could facilitate ACh release and enhance pyramidal cell excitability via diverse postsynaptic mechanisms, including inhibition of the M-current and the sAHP (Brown and Adams, 1980;Pitler and Alger, 1990;Krause and Pedarzani, 2000;Krause et al, 2002). Such actions could enhance complex spike probability (Azouz et al, 1996) and spike propagation into the dendrites (Tsubokawa and Ross, 1997), which is critical to the induction of 5 Hz LTP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that activation of group I mGluRs leads to a suppression of several types of potassium currents, including slowly inactivating D-type outward currents (I D ) and apamin-insensitive currents responsible for the slow afterhyperpolarization in hippocampal neurons (Krause et al 2002;Wu and Barish 1999), M-type potassium currents in superior cervical ganglion neurons (Ikeda et al 1995), and 4-AP-sensitive transient currents and 4-AP-insensitive potassium currents in visceral sensory neurons (Hay and Lindsley 1995). In particular, group I mGluRs have been shown to inhibit background potassium currents in cholinergic interneurons, which induces membrane depolarization (Berg et al 2007;Bonsi et al 2005;Takeshita et al 1996).…”
Section: Pkc Modulation Of Kv Channelsmentioning
confidence: 99%